2007
DOI: 10.1016/j.bbamem.2006.11.004
|View full text |Cite
|
Sign up to set email alerts
|

The properties of Bacillus cereus hemolysin II pores depend on environmental conditions

Abstract: Hemolysin II (HlyII), one of several cytolytic proteins encoded by the opportunistic human pathogen Bacillus cereus, is a member of the family of oligomeric beta-barrel pore-forming toxins. This work has studied the pore-forming properties of HlyII using a number of biochemical and biophysical approaches. According to electron microscopy, HlyII protein interacts with liposomes to form ordered heptamer-like macromolecular assemblies with an inner pore diameter of 1.5-2 nm and an outer diameter of 6-8 nm. This i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
44
0
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 31 publications
1
44
0
5
Order By: Relevance
“…In concert with these in vitro data, we showed that expression of HlyII in B. subtilis renders this organism virulent for the crustacean Daphnia magna (36) and leads to membrane damage in the alga Chara corallina (25); the role of HlyII in the virulence of B. thuringiensis in mice and insects was demonstrated by others (40). The toxic properties of HlyII rely on its ability to disrupt cellular and artificial membranes by pore formation (3). The prevalence of the hlyII genes among various B. cereus pathogenic strains is a significant indicator of their potential importance in virulence and pathogenesis (11).…”
supporting
confidence: 53%
See 1 more Smart Citation
“…In concert with these in vitro data, we showed that expression of HlyII in B. subtilis renders this organism virulent for the crustacean Daphnia magna (36) and leads to membrane damage in the alga Chara corallina (25); the role of HlyII in the virulence of B. thuringiensis in mice and insects was demonstrated by others (40). The toxic properties of HlyII rely on its ability to disrupt cellular and artificial membranes by pore formation (3). The prevalence of the hlyII genes among various B. cereus pathogenic strains is a significant indicator of their potential importance in virulence and pathogenesis (11).…”
supporting
confidence: 53%
“…Thus, it was no surprise that the overall expression profiles of hlyII and hlyII-lacZ were different but both hlyII-lacZ promoter activity and specific HlyII hemolytic activity were repressed 2-to 3-fold by 0.3 mM FeCl 3 . Variation of Fe concentrations in the range of 0.1 to 0.3 mM FeCl 3 did not affect the repression level.…”
Section: Fur Operator Phlyii Is Found In Many B Cereus Genomesmentioning
confidence: 99%
“…InhA1, NprA, and HlyII may play a role in addition to the enterotoxins. InhA1 and NprA are proteases cleaving various membrane components (11), and HlyII has cytotoxic and hemolytic activities (2). These properties may allow the bacteria to gain access to deeper tissues and to disseminate.…”
Section: Discussionmentioning
confidence: 99%
“…HlyII hemolytic activity toward rabbit blood cells is over 15 times more potent than that of Staphylococcus alpha-toxin (48). It forms heptameric pores in synthetic lipid bilayers and is hemolytic and cytotoxic to various human cell lines (2,3). HlyII induces apoptosis in human and mouse macrophages and is strongly implicated in B. cereus virulence toward mice and insects (S. Tran, E. Guillemet, C. Clybouw, A. Moris, M. Gohar, D. Lereclus, and N. Ramarao, submitted for publication).…”
mentioning
confidence: 99%
“…Concerning with the adverse environmental conditions, the hly gene may be switched on and express the virulence factors. Andreeva et al (2007) supported that, optimum temperature for HlyII expression and action is between 15 and 28 °C could use this weapon in the crustacean gut.…”
Section: Accepted Manuscriptmentioning
confidence: 82%